The role of education in building personal identity - Rahim, Dr. Aram Asad Abdul; Faiq, Sara Atta; Salahuddin, Hiwa (Sulaimani Journal for Humanities, 2025)
Identity is a complex and multidimensional concept. The development of a complex and stage-dependent process involves several different stages, programs, characters and processes. One of the tasks of education programs, apart from their scientific and professional tasks, is that the programs work in a multidimensional and broad perspective in order to build an appropriate identity for any time and place. The program (Social Skills and Values) is considered an important part of the education process in South Kurdistan and is given to students at all stages of primary education in schools under the Ministry of Education of the Kurdistan Regional Government. This research aims to analyze the impact of the education system on the formation of personal identity, to achieve this goal, the method (social survey) of the type of descriptive analytical survey is used, which is one of the methods of descriptive research. The study concluded: Programs are an important source of identity and high values. Through education, teachers and families, social skills and values programs have become a source of identity and the inculcation of social, moral and cultural values. Programs should be reviewed and changed to make them more effective and meet the needs of the new era in the formation of personal, ethnic, religious, social and professional identity.
Keywords: Role; education; identity; personal identity